Cruel Garden Ross Stretton's troubled season at the Royal Ballet - Mccarthy, Brendan (Dance Books Ltd., Alton,Hampshire (UK), 2002)
Ross Stretton's troubled year at the Royal Ballet. Ross Stretton belongs to the broader colonial tradition of British ballet, in a phrase, the insider's outsider. It was roght to experiment, right to risk failure. PALABRAS CLAVE: Ross Stretton, Royal Ballet, Michael Kaiser, Royal Opera House, Australian Ballet.